Mephedrone and Alcohol Interactions in Humans - Papaseit, Esther; Pérez-Mañá, Clara; de Sousa Fernandes Perna, Elizabeth B.; Olesti, Eulalia; Mateus, Julian; Kuypers, Kim PC; Theunissen, Eef L.; Fonseca, Francina; Torrens, Marta; Ramaekers, Jan G.; de la Torre, Rafael; Farré, Magí (Frontiers in Pharmacology, 2020)
Mephedrone (4-MMC, mephedrone) is a synthetic cathinone derivative included in the class of New Psychoactive Substances. It is commonly used simultaneously with alcohol (ethanol). The aim of the present study was to evaluate the interactions on subjective, cardiovascular and hormone effects and pharmacokinetics between mephedrone and alcohol in humans. Eleven male volunteers participated as outpatients in four experimental sessions in a double-blind, randomized, cross-over, and placebo-controlled clinical trial. Participants received a single oral dose of 200 mg of mephedrone plus 0.8 g/kg of alcohol (combination condition); 200 mg of mephedrone plus placebo alcohol (mephedrone condition); placebo mephedrone plus 0.8 g/kg of ethanol (alcohol condition); and placebo mephedrone plus placebo alcohol (placebo condition). Outcome variables included physiological (blood pressure, heart rate, temperature, and pupil diameter), psychomotor (Maddox wing), subjective (visual analogue scales-VAS, ARCI-49 item short form, and VESSPA questionnaire), and pharmacokinetic parameters (mephedrone and ethanol concentrations). The study was registered in ClinicalTrials.gov, number NCT02294266. The mephedrone and alcohol combination produced an increase in the cardiovascular effects of mephedrone and induced a more intense feeling of euphoria and well-being in comparison to the two drugs alone. Mephedrone reduced the sedative effects produced by alcohol. These results are similar to those obtained when other psychostimulants such as amphetamines and MDMA are combined simultaneously with alcohol. The abuse liability of mephedrone combined with alcohol is greater than that induced by mephedrone alone.